IMPROVING STUDENTS’ VOCABULARY OF SONG LYRICS THROUGH VIDEO CLIP - Ladan, Angela Pratiwi; Sada, Clarry; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed to improve students’ vocabulary of song lyrics through video clip to the class XI IIS 1 of SMA Negeri 1 Kelam Permai in Academic Year 2018/2019. The method used in this research was Classroom Action Research. The subject of this research was XI IIS 1 with 29 students. The tools of data collection were observational checklist table, field note, and test. This research was done in two cycles. The result from the data analysis showed that video clip could improve students’ vocabulary. Listening and reading to the song lyrics from the video clip could improve students’ spelling in written form and pronunciation achievement. Video clip had also improved the behavior of the students towards the teaching and learning process as can be seen from the students’ activeness in each cycle. It also can be seen from the improvement of the mean score in cycle 1 which was 60 became 82.5 in spelling test and from 73.21 became 84.64 in pronunciation test. This data showed that students’ achievement was improved significantly. As the conclusion, the researcher concluded that using video clip had successfully improved the students’ vocabulary especially in spelling in written form, and pronunciation.Keywords: Video Clips, Vocabulary Spelling and Pronunciation, Song Lyrics, Classroom Action Research.